149k views
3 votes
Khalid wrote the sequence below.

x-1, -2x+2, 4x-4, -8x+8

Which formula can be used to find the 10th term of the sequence?
A. a10=(x-1)*(-2)^10-1
B. a10=(x-1)^10-1
C. a10=(x-1)*(2)^10-1
D. a10=(x-1)*(-2)^10

User Lippoliv
by
5.6k points

2 Answers

7 votes
Formula A can help you find the 10th term.
I hope this Helps you
User David Fells
by
6.3k points
1 vote
ANSWER

The 10th term of the sequence can be found using the formula,


a_(10) =(x - 1)( - 2) ^( 10- 1)

Step-by-step explanation

The first four terms of the geometric sequence were given as,


(x-1),(-2x+2),(4x-4),(-8x+8)

We can determine the common ratio using any two subsequent terms.

The common ratio is,

r= ( - 2x + 2)/(x - 1)

This implies that,

r= ( - 2(x - 1))/(x - 1) = - 2

Also, the first term of the sequence is,


a_1=x - 1

The general term of the sequence is given by,


a_n=a_1(r) ^( n- 1)

We substitute the first term, the common ratio and
n= 10
in to the general term to get,


a_(10) =(x - 1)( - 2) ^( 10- 1)

The correct answer is option A.
User Yesnault
by
5.8k points